On the modularity of a lattice of τ-closed n-ultiply ω-composite formations - Vorob'ev, N. N.; Tsarev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
Let n ≥ 0, let ω be a nonempty set of prime numbers and let τ be a subgroup functor (in Skiba’s sense) such that all subgroups of any finite group G contained in τ (G) are subnormal in G. It is shown that the lattice of all τ-closed n-multiply ω-composite formations is algebraic and modular.